2010
DOI: 10.1177/0960327110369860
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning hormesis and the homeopathic Similia principle: Molecular aspects

Abstract: Postexposure conditioning, as a part of hormesis, involves the application of a low dose of stress following exposure to a severe stress condition. Depending on whether the low-dose stress is of the same type of stress or is different from the initial high-dose stress causing the diseased state, postconditioning can be classified as homologous or heterologous, respectively. In clinical homeopathy, the same distinction is found between isopathic and homeopathic application of low-dose substances. Homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 29 publications
1
77
0
Order By: Relevance
“…Low doses of nanoparticles can cause hormesis [105,123]. Other studies have demonstrated that low doses of homeopathically-prepared metals, including cadmium and arsenic, can produce beneficial hormetic reversal of effects of higher, toxic doses of the same or crosssensitized agent on heat shock protein activation patterns [124]. Heat shock proteins are among the biological modulators of the stress response networks involved in adaptation to various environmental stressors [94,125].…”
Section: Organism-dependent Response Amplification Phenomenamentioning
confidence: 99%
See 4 more Smart Citations
“…Low doses of nanoparticles can cause hormesis [105,123]. Other studies have demonstrated that low doses of homeopathically-prepared metals, including cadmium and arsenic, can produce beneficial hormetic reversal of effects of higher, toxic doses of the same or crosssensitized agent on heat shock protein activation patterns [124]. Heat shock proteins are among the biological modulators of the stress response networks involved in adaptation to various environmental stressors [94,125].…”
Section: Organism-dependent Response Amplification Phenomenamentioning
confidence: 99%
“…The reader is referred to other papers on these low dose, organismdependent response amplification phenomena for more in-depth explanations [21,99,119,120]. Given the quantum dot size of some homeopathically-prepared metal NPs [3], it is not also possible to rule out quantum mechanical phenomena in some of the homeopathicallyinduced low dose responses [147][148][149].…”
Section: Salient Signal For the Systemmentioning
confidence: 99%
See 3 more Smart Citations